Kursy e-learningowe – pakiety edukacyjne tworzone przez studentów - Kandzia, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Artykuł jest raportem z przeprowadzonych przez autorkę warsztatów pt. „Zastosowanie platformy e-learningowej do stworzenia zasobnika wiedzy dla potrzeb studentów Wydziału Nauk Pedagogicznych UKSW w Warszawie” realizowanych w ramach projektu „Nowoczesny pedagog”. Przedstawiono krótką charakterystykę kursu oraz analizę przyrostu wiedzy studentów w zakresie samodzielnego tworzenia kursu e-learningowego.

The article is a report from the workshop conducted by the author entitled: The use of an e-learning platform to create a reservoir of knowledge for the needs of Faculty of Pedagogical Sciences students at the UKSW in Warsaw, implemented under the project – Modern educator. Presented is short of the course and analysis of knowledge growthof students’ knowledge in the field of independent creation of an e-learning course.
E-learning Courses – Educational Packages Created by Students
Keywords: e-learning; platforma Moodle; kompetencje w kształceniu online; Moodle platform; competences in online education